2011
DOI: 10.1007/s10877-011-9287-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive cardiac output and oxygen delivery measurement in an infant with critical anemia

Abstract: Non-invasive continuous CO and CaO(2) monitors are shown in this single case to provide continuous DO(2) measurement. The ability to assess DO(2) may improve hemodynamic monitoring during goal directed therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We have presented a comprehensive account of the cardiovascular parameters in a cohort of children in “fluid resistant” septic shock during the first 42 h of bundle therapy in intensive care. Their severity of illness is indicated by the PIM2 scores ( 20 ). The titration of inotropes and vasopressors during treatment was assisted by non-invasive 6 hourly cardiac output monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…We have presented a comprehensive account of the cardiovascular parameters in a cohort of children in “fluid resistant” septic shock during the first 42 h of bundle therapy in intensive care. Their severity of illness is indicated by the PIM2 scores ( 20 ). The titration of inotropes and vasopressors during treatment was assisted by non-invasive 6 hourly cardiac output monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…This device estimates CO, CI, stroke volume (SV), SI, and a variety of other cardiac parameters using a complex mathematical algorithm (electrical velocimetry relates the maximum rate of change of impedance to peak aortic blood acceleration during the cardiac cycle) with the simple application of four EKG electrodes . The accuracy of this monitor has been validated and compared with other measures of CO such as the Fick equation , thermodilution , and echocardiography in diverse pediatric populations including patients with congenital heart disease and critical illness , neonates , and obese adolescents . One study of patients who had recovered from critical illness demonstrated a bias toward underestimation of CI and another found it to be useful in patients who had undergone cardiac surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Infants with RSV bronchiolitis represent an ideal population for use of this non-invasive CO monitoring device, which can offer an adjunct hemodynamic measure to HR and blood pressure in infants who may require referral to subspecialty units and/or tertiary care facilities for worsening clinical status. In infants with RSV bronchiolitis, the EC monitor is one of only a few methods that have been demonstrated to measure CO continuously [38] and non-invasively. CO monitoring in infants remains a clinical challenge [39,40].…”
Section: Discussionmentioning
confidence: 99%